Atividade física e acidentes por quedas em idosos que frequentam centro de convivência - Valim-Rogatto, Priscila Carneiro [UNIFESP] (2009)
The aims of this observational, cross-sectional study were: i) investigate the prevalence of accidental falls in Senior Citizen Centers (SCC) users and the influence of factors associated with these falls such as age group, sex, civil status, level of education, family/person income, retirement, labor market participation, cognitive status, registration period and activities carried out at SCC, and level of physical activity; ii) estimate the level of physical activity in this elderly population relating to the variables described above as well as the possible association with accidental falls; and iii) analyze the association among level of physical activity and related-factors and/or consequences on the most recent fall (number, daytime and fall location, fracture or injury occurrence, search for medical services and fear of falling). The sample included 350 Senior Citizens from three different SCC from Cuiabá City (Mato Grosso State, Brazil) that answered the Mini-mental State Examination–MMSE and the International Physical Activity Questionnaire-IPAQ short version. The Characterization of Falls Questionnaire was answered only by those elderly who had fallen. Descriptive Statistic, Binary Logistic Regression and Ordinal Logistic Regression by Proportional Odds Model (POM) were used for data analyses (p<0.05) from a 291 elderly sub-sample. About 40% of the elderly suffered falls in the last year. From this group, 45.3% declared to have fallen two or more times in the same period. The predictive model of falls was comprised by the following variables: female gender (OR= 5.12; IC= 2.48–10.56), 75-79 years old age group (OR=3.0; IC= 1.20–7.47), divorced marital status (OR=4.09; IC= 1.27–13.22), and to be pensioner (OR=2.82; IC= 1.20–6.64). Analyzing the level of physical activity (LPA), 38.1% of voluntaries were classified as high level, 49.8% as moderate level and 12.1% as low level. The results of POM indicated that the oldest group showed lower chance to be classified as high LPA (OR=0.78: IC=0.96-2.92) than elderly younger groups. Seniors that do not have a job (OR=0.38: IC=0.22–0.67) and those with low cognitive status (OR=0.31; IC=0.31-0.38) had little possibility to be in high LPA in opposition to the other levels. Regarding to the last fall reported, it was verified that 46.2% occurred in the afternoon, 9.4% resulted in fractures, 70.9% resulted in some sort of injury and 23.9% did not result in any impairments. It was also verified that 54.7% of the elderly suffered outdoor falls, 61.5% did not seek any medical attention and 43.6% related being very afraid of falling. In relation to the variables concerning to the last fall reported, results from MOP by NAF revealed that elderly that did not suffered injuries were more likely to be in high LPA (OR=8.19: IC= 1.00–66.74). Our results indicate that civil status, social security benefit receiving, sex and age were predictors to falls. Moreover, level of physical activity did not show any association with accidental falls occurrence.